Pendampingan Penerapan Manajemen Pada Komunitas Bank Sampah di Kabupaten Lampung Timur - Trisnawati A, Ika; Rahmawati, Rita (PT. ALHAFI BERKAH INDONESIA, 2024)
Waste thrown away by the community and business units will cause environmental problems, if it is not managed properly and correctly. All parties become responsible for the waste problem which is getting bigger as the population increases. Not only the government but the full participation of the community in managing household waste is very helpful in overcoming the waste problem. Apart from being expected to save the environment from pollution properly and correctly, waste management can also provide economic value, in the form of income from waste management. The existence of this economic value further motivates the community to get involved in waste management. Since 2017, East Lampung Regency, as one of the districts in Lampung Province, has provided support for waste management with Waste Bank Institutional Management. The East Lampung Regency waste bank community under the auspices of the East Lampung Regency Environment, Settlement and Land Service, is an example of a community that actively carries out waste management activities with the community. In terms of management, it is still traditional and has not yet implemented an effective and efficient management system. Every organization will achieve its goals by implementing a management system that has been established if the economic functions of management are implemented within it. The economic functions of management consist of 4 main activities, namely Planning, 2 Organizing, 3 Actuating (Directing) and Controlling (Supervision). The aim of this assistance is the application of economic management functions, so that all activities in the Waste Bank Community will be orderly, focused in achieving the set goals. Using the ABCD Method is the right method to realize this. The result of this service is waste bank management training which consists of Planning, Organizing, Implementing, directing, controlling and supervising the aim of increasing capabilities. and the creativity of the Waste Bank management. This waste bank management will realize and achieve the general goals and specific goals of each waste bank, traditional management.